Probiotics-derived metabolite ameliorates skin allergy by promoting differentiation of FOXP3+ regulatory T cells - Kang, H.-J.; Kim, G.-C.; Lee, C.-G.; Park, S.; Sharma, G.; Verma, R.; Im, S.-H.; Kwon, H.-K. (Mosby Inc., 2021)
[No abstract available]